Investigation of the influence of tool-sided parameters on deformation and occurring tool loads in shear-clinching processes - Han, Daxin; Hörhold, Réjane; Wiesenmayer, Sebastian; Merklein, Marion; Meschut, Gerson (Procedia Manufacturing, 2018)
Shear-clinching is a method for joining of dissimilar materials without auxiliary element. The technology combines shear-cutting and clinching in one process. Challenges of the process are the deformation of the specimens and the high process forces, which lead to high tool loads. Thus, the influence of the punch-sided tool geometry on the deformation of multi-element specimens was tested experimentally within this study. The effect of the geometrical changes on the occurring tool loads was analysed with a numerical model in order to evaluate the benefit of the adapted design with regard of the lifetime of the toolset.
LFT Import::2019-07-29 (2321)
Keywords: Clinching; Deformation of specimen; Joining by forming; Lightweight; Multi-material design; Tool load